Financial `metrics for comparing Australian retirement villages. (10th March 2021) - Kyng, Timothy; Pitt, David; Purcal, Sachi; Zhang, Jinhui
Abstract: Retirement village contracts are complex, blending together financial options on real estate, life annuities and life insurance. We analyse the structure of the cash flows involved in a retirement village contract and distil the cost components into an equivalent monthly comparison rent. In general, we observe lower monthly rents when the maintenance fees and deferred management fees are lower, when higher rates of capital gain are evident, and, importantly, when retirees reside in the retirement village for a longer period. Our analysis provides a framework to meaningfully compare the relative merits of the finances incorporated into retirement village contracts.